GENETIC DIVERGENCE IN DOUBLED HAPLOID LINES OF SPRING WHEAT (Triticum aestivum L.) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
Genetic divergence of 17 doubled haploid lines and 3 check varieties of spring wheat were assessed through Mahalanobis D2-statistics. The genotypes were grouped into six clusters. The clusters I and III contained the highest number of lines (5). The cluster V contained single genotype. The maximum inter-cluster distance was noticed between the clusters I and V and minimum between III and VI. The highest intra-cluster distance was observed in the cluster IV and lowest in the cluster V.DOI: http://dx.doi.org/10.3329/bjpbg.v20i2.17034